2005
DOI: 10.1097/01.aco.0000174959.05383.9c
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in anaesthesia and pain therapy

Abstract: In general, the results of the very few well-conducted clinical trials often diverge from the highly interesting and promising findings of preclinical studies. Taken together, the most recent preclinical and clinical data suggest that cannabinoids should be applied as low-dose co-analgesics to inhibit neuroplasticity and central sensitization rather than as analgesics in acute pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The most important clinically applied cannabinoid is ⌬ 9 -THC. Among others, this substance is known to have analgesic, sedative, and mood improving properties, which are useful in cancer patients suffering from pain and fear (Azad and Rammes 2005). In the present study we found that ⌬ 9 -THC significantly reduces LTD induction.…”
Section: +supporting
confidence: 66%
“…The most important clinically applied cannabinoid is ⌬ 9 -THC. Among others, this substance is known to have analgesic, sedative, and mood improving properties, which are useful in cancer patients suffering from pain and fear (Azad and Rammes 2005). In the present study we found that ⌬ 9 -THC significantly reduces LTD induction.…”
Section: +supporting
confidence: 66%
“…Nevertheless, preclinical and clinical data suggest that lower doses of cannabinoids may be effective for the treatment of allodynia and hyperalgesia in neuropathic pain. It seems that cannabinoids should be applied as low-dose co-analgesics to inhibit neuroplasticity and central sensitization rather than as analgesics in acute pain [1] . It is concluded that the stimulation of both CB-1 and CB-2 receptors inhibited transmission of pain stimuli in STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…
development of new experimental methods during the past several decades has made it possible to understand the mechanisms of cannabinoid action [1,2] . The existence of endogenous ligands for cannabinoid receptors, e.g.
…”
mentioning
confidence: 99%
“…In recent years, there has been renewed interest in the use of cannabis for analgesic purposes because of the favorable safety profile of cannabinoids (a group of terpenophenolic compounds present in Cannabis sativa that bind to cannabinoid receptors) [135]. There have been no reported deaths directly attributed to cannabis overdose.…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Although it is not similarly licensed in the UK, it can be imported from Canada for named-patient prescription use. Unfortunately, Review Hill & Schug cannabinoids do not seem to be effective in postoperative pain management being only moderately effective, no different from placebo or even antanalgesic at high doses [135].…”
Section: Cannabinoidsmentioning
confidence: 99%